28. STUDY ON CLINICAL, PARACLINICAL CHARACTERISTICS AND TREATMENT RESULTS OF DUODENAL TRAUMA IN CHILDREN (Vietnam Journal of Community Medicine, 2025)
Objective: To analyze the clinical and paraclinical characteristics, and treatment results of duodenal trauma in children at Children's Hospital 2.Subjects and Methods: A retrospective case series study was conducted on 15 pediatric patients treated with duodenal trauma at General Sugery Department, Children's Hospital 2, from January 2014 to June 2024.Results: 15 cases of duodenal trauma were identified: 14 cases of blunt duodenal injury and only 1 case of penetrating injury. Most are grade II duodenal lesions according to AAST. Computed tomography aided diagnosis in most cases of blunt duodenal injuries. 3 cases were successfully treated conservatively. 12 cases required surgical intervention: 7 cases were treated with simple duodenal perforation suture, 1 case of duodenal serosa incision to drain the hematoma, 2 cases were treated with Roux-en-Y duodenojejunostomy, 2 cases of duodenal hematoma were detected during surgery, the serosa was not incised to drain the hematoma but only a decompression tube was placed. All cases had duodenal decompression tube placed.Conclusions: Duodenal trauma in children is a rare and complex injury. Most are due to blunt abdominal trauma and are grade II - AAST. Computed tomography plays an important role in supporting the diagnosis of duodenal trauma. Duodenal decompression tube placement in conservative treatment or surgical intervention helps achieve good treatment results.
Keywords: Duodenal trauma, American Association for the Surgery of Trauma (AAST).